FLOWERING AND FRUIT PRODUCTION OF PINEAPPLE IMPROVE WITH ACTIVATED CARBON AND ETHYLENE (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
Pineapple fruit production (Ananas comosus L. Merr.) is negatively affected by inhomogeneous natural flowering, but flowering can be exogenously induced by growth regulators such as Ethephon (2-chloroethylphosphonic acid), resulting in greater production and yield in this crop. Thus, this study aimed to evaluate the application of Ethephon and ethylene + activated carbon to increase flowering and the qualitative and yield components of pineapple. The experiment was set up in a randomized block design with three treatments and five replications (blocks). After checking that the variance of the data sets was homogeneous, they were subjected to analysis of variance. Subsequently, the difference between the means of the treatments was determined using the Tukey test (P ≤ 0.05). There was a significant difference in costs and gains between using and not using flowering inducers, representing a significant difference in the benefit-cost ratio (BCR). Therefore, the use of activated carbon + ethylene proved to be economically viable. We conclude that activated carbon associated with ethylene provided a higher percentage of flowering in pineapple fruit. However, this inducer and Ethephon were similarly effective in increasing yield in this crop.